2015
DOI: 10.1089/scd.2015.0031
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of a Homozygous Human Androgenetic Embryonic Stem Cell Line

Abstract: Human embryonic stem cells (hESCs) have long been considered as a promising source for cell replacement therapy. However, one major obstacle for the use of these cells is immune compatibility. Histocompatible human parthenogenetic ESCs have been reported as a new method for generating human leukocyte antigen (HLA)-matched hESCs. To further investigate the possibility of obtaining histocompatible stem cells from uniparental embryos, we tried to produce androgenetic haploid human embryos by injecting a single sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 32 publications
(38 reference statements)
2
17
0
1
Order By: Relevance
“…Our SNP analysis showed 99.53% homozygosity in AgFibs, 99.48% in AgHiPSCs, and 72.72% in H9 cells. According Ding et al 9 , human AgESCs were 99.39% homozygous, in contrast to 72.85% homozygosity in H9 cells. These data confirmed that our androgenetic cell lines were homogeneous.…”
Section: Discussionmentioning
confidence: 98%
“…Our SNP analysis showed 99.53% homozygosity in AgFibs, 99.48% in AgHiPSCs, and 72.72% in H9 cells. According Ding et al 9 , human AgESCs were 99.39% homozygous, in contrast to 72.85% homozygosity in H9 cells. These data confirmed that our androgenetic cell lines were homogeneous.…”
Section: Discussionmentioning
confidence: 98%
“… successfully generated haESCs from Macaca fascicularis monkey parthenotes. Nevertheless, preliminary attempts to derive human haESCs resulted in a homozygous diploid AG ESC line ; thus whether haESCs can be derived from humans remains an open question.…”
Section: Generation Of Haescs From Other Mammalian Speciesmentioning
confidence: 99%
“…Recently, by combined application of a modified single-cell enzymatic dissociation method [37][38][39] and regular cell sorting, Yang et al [40] successfully generated haESCs from Macaca fascicularis monkey parthenotes. Nevertheless, preliminary attempts to derive human haESCs resulted in a homozygous diploid AG ESC line [41]; thus whether haESCs can be derived from humans remains an open question.…”
Section: Generation Of Haescs From Other Mammalian Speciesmentioning
confidence: 99%
“…In addition, cynomolgus monkey ESCs with higher pluripotency with which monkey chimeric fetuses were generated have been obtained . Human parthenogenetic ESCs Shuai et al, 2015) and homozygous human androgenetic ESCs (Ding et al, 2015) were derived, providing important tools for future therapeutic use in a clinical setting.…”
Section: Pluripotent Stem Cells: Higher Pluripotency and Closer To Humanmentioning
confidence: 99%